2019
DOI: 10.1002/tox.22762
|View full text |Cite
|
Sign up to set email alerts
|

3‐Methyladenine alleviates excessive iodine‐induced cognitive impairment via suppression of autophagy in rat hippocampus

Abstract: Drinking water with high levels of iodine has been identified as the key contributor to iodine excess, but the mechanisms of neurotoxicity induced by excessive iodine remain elusive. The present study aimed to explore the role of autophagy in the neurotoxic effect induced by excessive iodine in vivo. The Morris water maze test results demonstrated that excessive iodine impaired the learning and memory capabilities of rats, which were associated with marked body weight and brain weight abnormalities. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…It occurs under conditions such as stress and hunger in the cell. It has been reported that 3-MA relieves cognitive impairment by suppressing autophagy in the rat hippocampus (Zhao et al, 2019). Considering the autophagy inhibiting effect of 3-MA, it did not cause any change in NOS enzyme levels after CIS administration.…”
Section: Discussionmentioning
confidence: 81%
“…It occurs under conditions such as stress and hunger in the cell. It has been reported that 3-MA relieves cognitive impairment by suppressing autophagy in the rat hippocampus (Zhao et al, 2019). Considering the autophagy inhibiting effect of 3-MA, it did not cause any change in NOS enzyme levels after CIS administration.…”
Section: Discussionmentioning
confidence: 81%
“…Using Sprague-Dawley rats exposed to excess iodine from pregnancy to 6 months post-delivery as in vivo model, Cui et al showed that excess iodine (5000 μg/L KIO 3 ) could change the hippocampal cell structure, activate the mitochondrial apoptosis pathway and damage the spatial learning and memory capacities in offspring of both genders [ 38 ]. Zhao et al reported that the male offspring were given 5000 μg/L KIO3 from PN0 to 8 weeks of age, ecxess iodine treatment increased malondialdehyde accumulation, decreased superoxide dismutase activity and glutathione (GSH) level, and enhanced levels of autophagy markers in the hippocampus, including LC3, Beclin1, and p62, and impaired the learning and memory capabilities [ 39 ]. Liu et al studied that a total of 1229 students aged between 8 and 10 years were recruited with a mean IQ of 105.8 in Tianjin, China, children who resided in regions with a very high water iodine concentration (234.7 μg/L), there was on average a reduction of IQ by nearly nine points in comparison with those who resided in a non-high water iodine area [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…3 Similarly, excessive intake of iodine can induce goiter, hyperthyroidism, or hypothyroidism in addition to triggering autoimmune thyroid disease (AITD). 4,5 AITD is an organ-specific autoimmune disease in which thyroid autoassociated antigens are activated, mainly in Graves' disease (GD) and Hashimoto's thyroiditis (HT). HT, also known as autoimmune thyroiditis (AIT), is the main cause of hypothyroidism, which is mainly characterized by lymphocyte infiltration into the thyroid gland.…”
Section: Introductionmentioning
confidence: 99%